Converting-enzyme inhibitor enalapril (MK421) in treatment of hypertension with renal artery stenosis. Issue 6356 (11th December 1982) - Hodsman, G P; Brown, J J; Davies, D L; Fraser, R; Lever, A F; Morton, J J; Murray, G D; Robertson, J I
Abstract : Enalapril maleate (MK421), a new inhibitor of angiotensin converting enzyme, in single daily doses of 1.25-40 mg was assessed in five patients with hypertension and renal artery stenosis. Only small falls in plasma angiotensin II concentrations were seen at doses less than 10 mg; even with 10 and 20 mg, angiotensin II concentrations had risen again 24 hours from the last dose. During long-term treatment with 10-40 mg daily all patients achieved good blood-pressure control. No significant changes of body sodium or potassium values were seen. The drug was well tolerated with no serious side effects. These findings are evidence of the efficacy and acceptability of enalapril in the medical management of hypertension with renal artery stenosis.